2016
DOI: 10.1097/qad.0000000000000918
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy induces a rapid increase in bone resorption that is positively associated with the magnitude of immune reconstitution in HIV infection

Abstract: Objective Antiretroviral therapy (ART) paradoxically intensifies bone loss in the setting of HIV-infection. Although the extent of bone loss varies, it occurs with virtually all ART types, suggesting a common pathway that may be aligned with HIV disease reversal. Using an animal model of immunodeficiency we recently demonstrated that immune activation associated with CD4+ T cell reconstitution induces increased production of the osteoclastogenic cytokines RANKL and TNFα by immune cells, driving enhanced bone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 50 publications
3
78
0
2
Order By: Relevance
“…[26, 27] Although severe immune reconstitution inflammatory syndrome (IRIS) is not common in pregnancy, the fetal effects of maternal immune reconstitution during pregnancy (particularly among women with advanced disease initiating potent ART) are not clear. The risk of ART-related bone resorption in HIV-infected adults appears to be highest among those initiating treatment at advanced disease stages,[6, 28] and a similar relationship may exist between disease severity at ART initiation in pregnancy and subsequent infant health outcomes. HIV disease severity is also associated with increased risk of maternal cytomegalovirus (CMV) reactivation, which increases the risk for congenital CMV and in turn, growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…[26, 27] Although severe immune reconstitution inflammatory syndrome (IRIS) is not common in pregnancy, the fetal effects of maternal immune reconstitution during pregnancy (particularly among women with advanced disease initiating potent ART) are not clear. The risk of ART-related bone resorption in HIV-infected adults appears to be highest among those initiating treatment at advanced disease stages,[6, 28] and a similar relationship may exist between disease severity at ART initiation in pregnancy and subsequent infant health outcomes. HIV disease severity is also associated with increased risk of maternal cytomegalovirus (CMV) reactivation, which increases the risk for congenital CMV and in turn, growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group examined bone turnover in treatment naïve HIV-infected patients initiating cART. We observed a surge in bone resorption, starting as early as 2 weeks after cART initiation and lasting through 24 weeks [68**]. Because T-cell recovery with cART reaches a significant magnitude by 12 weeks [69], the time point at which we observed a peak in bone resorption, we speculated that there was a link between immune reconstitution and cART-induced bone loss [68**].…”
Section: Hiv Disease Reversal and Immune Reconstitutionmentioning
confidence: 99%
“…We observed a surge in bone resorption, starting as early as 2 weeks after cART initiation and lasting through 24 weeks [68**]. Because T-cell recovery with cART reaches a significant magnitude by 12 weeks [69], the time point at which we observed a peak in bone resorption, we speculated that there was a link between immune reconstitution and cART-induced bone loss [68**]. Using an animal model of immune reconstitution created by adoptive transfer of T-cells into T-cell knock-out mice, we demonstrated that immune reconstitution did indeed result in a profound loss in BMD via activation of T-cells and/or other immune cells leading to RANKL and/or tumor necrosis factor-alpha (TNF-α) production [70*].…”
Section: Hiv Disease Reversal and Immune Reconstitutionmentioning
confidence: 99%
“…Pilot data from a study of treatment-naive HIV-infected patients on therapy for 24 weeks with lopinavir/ritonavir + TDF/ FTC [14] form the basis for estimating sample size. Assuming an increase on average of 1.2 µg/L for CTx in the active placebo arm and on average no change in the ZOL arm and an estimated standard deviation in each group of 1.4 µg/L, a sample size of 30 patients per treatment arm achieves 90% power to detect a treatment difference of 1.2 µg/L in CTx between active placebo and ZOL at 24 weeks if the true difference between treatments is 1.2 µg/L (2-sided, 2-sample equal-variance t test and α = .05).…”
Section: Sample Size and Power Considerationsmentioning
confidence: 99%
“…To better understand the mechanism underlying this phenomenon, we previously examined bone turnover in HIVinfected patients initiating ART, and observed a surge in bone resorption, starting as early as 2 weeks and lasting through 24 weeks [14]. Because T-cell recovery with ART reaches a significant magnitude by 12 weeks [15], the time point at which we observed a peak in bone resorption, we speculated that there was a link between immune reconstitution and ART-induced bone loss.…”
mentioning
confidence: 99%